Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Reclaiming female agency: feminist art history after postmodernism - Broude, Norma..; Garrard, Mary D.; Broude, Norma; Garrard, Mary D. (University of California Press, 2005)
This volume is the third in an influential series of anthologies by editors Norma Broude and Mary D. Garrard that challenge art history from a feminist perspective. Following their Feminism and Art History: Questioning the Litany (1982) and The Expanding Discourse: Feminism and Art History (1992), this new volume identifies female agency as a central theme of recent feminist scholarship. Framed by a lucid and stimulating critical introduction, twenty-three essays on artists and issues from the Renaissance to the present, written in the 1990s and after, offer a nuanced critique of the poststructuralist premises of 1980s feminist art history.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; thématiques